PERAN MEDIA SOSIAL SEBAGAI WADAH ASPIRASI MASYARAKAT - Tranggono Tranggono; Muhammad Rizqi Dhuhri; Dzulfikri Ali Zidan Qusyairi; Nasywa Anindya Puspa; Tsanya Kamila Syawalita; Daffa Maulidia Artanti; Erinda Wahyu Kusumaningrum (Gapenas Publisher, 2023)
Social media has become an inseparable part of people's daily lives in Indonesia and even in the world. One of the social media that is currently very popular among the public is TikTok. In fact, TikTok is the top 3 most downloaded application in 2022, with a total of 500 million+ downloads. People use TikTok for all kinds of things. One of them is to criticize the progress of regional infrastructure. The government often underestimates the damage and lack of regional infrastructure. In this article, we examine how people use TikTok social media as a tool in criticizing the progress of regional infrastructure. This research is based on a viral video from the awbimax reborn account which discusses the progress of the Lampung area where the video contains quite scathing criticisms. This research was conducted using a qualitative approach by conducting questionnaires and observations of a number of parties involved in making and disseminating the video. The result is that many people use social media such as TikTok as a means to criticize and voice their disappointment with the progress of regional infrastructure which is considered to be still very minimal